2011
DOI: 10.1262/jrd.10-092n
|View full text |Cite
|
Sign up to set email alerts
|

Identifying mRNAs Bound by Human RBMY Protein in the Testis

Abstract: Abstract. Rbmy gene encodes a germ-cell specific nuclear RNA-binding protein and is involved in spermatogenesis. To further investigate the specific events of spermatogenesis in which Rbmy plays a role, the target mRNAs of human RBMY protein were isolated and identified. Through the isolating specific nucleic acids associated with proteins (SNAAP) technique, we isolated twenty potential target genes of human RBMY protein from the human testis in the present study. Some of these target genes play important role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…S9). Targeting its own mRNA in testis for alternative splicing (Zeng et al 2008(Zeng et al , 2011, these severe defects may be attributed to expression of RBMY1A1 in the unnatural embryonic environment. Indeed, analysis of RNA sequencing (RNA-seq) reads revealed a number of gene products with exon-skipping events, which was validated for three genes (Scamp4, Mettl6, and Mybl2) by RT-PCR in individual embryos of both sexes and genotypes (Supplemental Table 4; Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S9). Targeting its own mRNA in testis for alternative splicing (Zeng et al 2008(Zeng et al , 2011, these severe defects may be attributed to expression of RBMY1A1 in the unnatural embryonic environment. Indeed, analysis of RNA sequencing (RNA-seq) reads revealed a number of gene products with exon-skipping events, which was validated for three genes (Scamp4, Mettl6, and Mybl2) by RT-PCR in individual embryos of both sexes and genotypes (Supplemental Table 4; Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…RBMY protein harbors an RNA recognition motif (RRM) and functions as a regulator of germ cell‐specific splicing events 24‐27 . Although it shares a conserved RRM domain with its X homolog RBMX, they diverged at their flanking sequences.…”
Section: Discussionmentioning
confidence: 99%
“…RBMY is predominantly expressed in the male germ cells under normal conditions 15,23 . The encoded protein harbors an RNA‐binding motif and could participate in RNA splicing events in germ cells of the testis 24‐27 . Deletions in the RBMY genes cause failure in male meiosis, resulting in the absence of mature sperms in the testes of infertile patients 23 .…”
Section: Introductionmentioning
confidence: 99%
“…This well conserved protein is also linked to male infertility, and it specifically associates with the mRNA of proteins necessary for spermatogenesis further establishing the role of RMBY1A1 and male germline specific splicing as critical to spermatogenic function [139][140][141]. Identifying other mRNA regulatory proteins, and their target mRNAs, will extend our basic biological understanding of SSCs and spermatogenesis beyond the transcriptome.…”
Section: Rna Regulation In the Male Germlinementioning
confidence: 94%
“…It further is an attractive candidate for clinical study of male infertility, because mutations in its genomic locus are associated with oliogospermgia and sperm abnormalities [137, 139]. Known for its role in mRNA splicing, studies in both mouse and human have identified RBMY1A1 target transcripts, many of which are alternatively spliced and some of which are testis specific, such as Tex14 [140,141]. These data imply a splicing role for RBMY1A1 in spermatogonia, and again, validate the study design.…”
Section: Dazlmentioning
confidence: 99%